Crossbreeding in literature in Algeria : itinerary of a notion - (:unkn) unknown (My University, 2020)
Our research is interested in cultural mix in French speaking literature of North Africa. It is a comparative study between literary works belonging to two different historical periods: Colonial period based on the works of Bertrand, les Algerianiste, Alger School and North African novelists of 1952 generation. And post-colonial through our analysis of novel ‘‘beur’. The objective of this research is to show how cultural mix becomes a source of literary inspiration. How a plural membership becomes a factor of literary creation? A culturally hybrid person bring together visions and values belonging to two worlds, and two different cultures mixed since childhood. The works of culturally hybrid writers reveal this mixture but, mainly, they show us how the culturally hybrid man manage to reconcile in him distinct values. This is what we call identity malaise. Indeed, this disturbing voice asks questions about the past and the future. Our objective, through this research works, is to look closely at the dialogue of cultures and civilizations, between East and West, between France and the Maghreb. Wish to revisit the Franco-algerian cultural heritage.
Keywords: African Research